Teenage sexual harassment - Rosnick, Emily; Jones, Constance; Educational Video Network (Texas: Educational Video Network, 2002)
The program explains how to recognize and deal with sexual harassment. Discover the permanent consequences of the devastating problem.
Executive producer, George H. Russel
Host: Linda Mares
Keywords: Sexual harassment; Sexual Harassment -- prevention & control